Division of labor, organizational coordination and markt mechanism in collective problem-solving - Luigi Marengo; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
This paper builds upon a view of economic system and individual economic organization as problem-solving arrangements and presents a simple model of adaptive problem-solving driven by trial-and-error and collective selection. The institutional structure, and in particular its degree of decentralization, determines which solutions are tried out and undergo selection. It is shown that if the design problem at hand is complex (in term of interdependencies between the elements of the system) then a decentralized institutional structure is very unlikely to ever generate optimal solutions and therefore no selection process can ever select them. We also show that nearly-decomposable structures have in general a selective advantage in terms of speed in reaching good locally optimal solutions.
Keywords: 330; Theory of the firm; Vertical and horizontal integration; Computational complexity; Arbeitsteilung; Theorie der Unternehmung; Organisationsstruktur; Marktmechanismus; Theorie